An analysis of preservice teachers critical thinking skills at Universitas Islam Balitar - Marinda Sari Sofiyana; Mar`atus Sholihah (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
The industrial revolution 4.0 in the 21st century presents its own challenges for all groups, including preservice teachers, to be able to quickly adapt to the progress of the times and technology, and solve all problems quickly, precisely, and wisely. To face the challenges of the 21st century, students need good critical thinking skills. By possessing good critical thinking skills, students can plan, monitor, and evaluate the steps they take both in learning activities and in problem solving. This study aims to describe the critical thinking skills of preservice teachers at the Faculty of Teacher Training and Education (FKIP) of Universitas Islam Balitar. This survey research was conducted in April–August 2020 with a total sample of 118 students from the Biology Education, Pancasila and Civic Education, English Education, and Elementary School Teacher Education study programs. Critical thinking skills were measured by an essay test and analyzed with the critical thinking rubric developed by Zubaidah et al. The data were analyzed descriptively. The results showed that the students' critical thinking skills were in the underdeveloped category.